2018
DOI: 10.1111/sdi.12698
|View full text |Cite
|
Sign up to set email alerts
|

Is the management of diabetes different in dialysis patients?

Abstract: Diabetes is highly and increasingly prevalent in the dialysis population and negatively impacts both quality and quantity of life. Nevertheless, the best approach to these patients is still debatable. The question of whether the management of diabetes should be different in dialysis patients does not have a clear yes or no answer but is divided into too many sub-issues that should be carefully considered. In this review, lifestyle, cardiovascular risk, and hyperglycemia management are explored, emphasizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 103 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…A study has shown that DPP-4 inhibitors combined with insulin can better reduce glycated hemoglobin (HbA1C) and insulin doses without increasing hypoglycemic events 17 . Some studies suggest that single or combined usage of DPP-4 inhibitors in patients with type 2 diabetes and CKD can ameliorate glycemic control without increasing AEs [18][19][20][21] . DPP-4 inhibitors also have renal protective effects and do not affect weight [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that DPP-4 inhibitors combined with insulin can better reduce glycated hemoglobin (HbA1C) and insulin doses without increasing hypoglycemic events 17 . Some studies suggest that single or combined usage of DPP-4 inhibitors in patients with type 2 diabetes and CKD can ameliorate glycemic control without increasing AEs [18][19][20][21] . DPP-4 inhibitors also have renal protective effects and do not affect weight [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on a similar population, a pilot study suggested that adding teneligliptin—another DPP‐4 inhibitor—to insulin decreased the incidence of hypoglycaemic episodes assessed by CGM, although insulin doses were voluntarily reduced by about a third from the first day of teneligliptin administration. A variable proportion of patients with diabetes undergoing haemodialysis may require insulin treatment, depending on the country and hospital, as well as on the practices that are specific to each diabetologist or nephrologist . Therefore, this study involving haemodialysed patients with type 2 diabetes sought to evaluate the effects of adding vildagliptin to insulin therapy on (i) glucose profiles using CGM and (ii) global metabolic control.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous research studies have been conducted in these areas, the use of surrogate outcomes and conflicting research results have left clinicians with little in the way of a unified or evidence‐based approach. To open this topic, the lifestyle, cardiovascular risk, and hyperglycemia management of diabetes in dialysis patients vs the general population is explored by Coelho . Dhillon‐Jhattu and Sprague then tackle the dilemma of hyperphosphatemia in the patient on dialysis, discussing pitfalls of the current guidelines and when and how to provide management .…”
mentioning
confidence: 99%